Use of Carbon Black as Filler in Asphalt Concrete - Ahmedzade, Perviz; Alatas, Taner; Geckil, Tacettin (Turkish Chamber Civil Engineers, 2008)
In this study, the using of carbon black as filler in asphalt concrete was investigated. Asphalt concrete mixtures where carbon black and limestone fillers having the same aggregate gradation were prepared and optimum bitumen content was determined by the Marshall stability test. Mechanical characteristics of the carbon black and control mixtures were evaluated with Marshall stability, indirect tensile stiffness modulus, creep stiffness and indirect tensile strength tests. The results obtained from the tests showed that carbon black improved mechanical properties and utility of asphalt concrete.
Asfalt betonunda siyah karbonun filler olarak kullanimi